Metabolite profiling of agarwood (Gyrinops versteegii (Gilg.) Domke) leaves from difference growth locations using Thin Layer Chromatography - Dwi Indriani Manurung; Lisna Hidayati; Nastiti Wijayanti; Tri Rini Nuringtyas (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Gyrinops versteegii (Gilg) Domke is an agarwood-producing plant originating from Eastern Indonesia. Leaves have antioxidant and anticancer activity due to their secondary metabolites. However, secondary metabolites are strongly influenced by the environment. This study aims to compare the terpenoid, phenolic, and flavonoid profiles of agarwood leaves grown in three locations, namely Bogor, Mataram, and Sambas using Thin Layer Chromatography (TLC), in order to obtain the most potential agarwood G. versteegii for further development as herbal medicine. Agarwood leaf powder was extracted using Soxhlet with 80% methanol as solvent, followed by liquid-liquid fractionation using chloroform and aquadest. The crude extract and the obtained fraction were subjected to metabolite profiling using TLC. Racing data factors from TLC were analyzed using hierarchical cluster analysis (HCA). The results showed that the Mataram sample produced higher yields for both extracts and fractions. TLC detected that the chloroform fraction contained more terpenoids, followed by phenolics and flavonoids, while the aqueous fraction contained the same number of positive bands for terpenoids and phenolics. In terms of origin, the Bogor sample showed six terpenoid positive bands higher than the other samples. A similar pattern was observed in the phenolics, while the flavonoids were the same for all samples. HCA resulted in Mataram being clustered separately from the Bogor and Sambas samples. Agarwood leaves from Mataram cannot be used to replace agarwood leaves from Bogor and Sambas as herbal ingredients.